Layered oxide material, preparation method and application of sodium ion battery positive electrode material
By introducing cobalt into the layered oxide material, the transition metal-oxygen covalent bond is enhanced, the problems of irreversible redox and lattice oxygen loss of the positive electrode material of sodium ion battery are solved during charging and discharging, and high energy density and Excellent cycle performance.
Patent Information
- Application Number
- CN202411284804.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-15
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-10
AI Technical Summary
The existing layered sodium ion battery positive electrode materials have irreversible redox and loss of lattice oxygen during charging and discharging, resulting in structural rearrangement and poor reversibility, affecting energy density.
Na0.7[Li0.2Mn0.7Co0.1]O2 is used as a layered oxide material, and prepared by solid phase method, cobalt is introduced to enhance transition metal-oxygen covalent bonds, inhibit the release of oxygen molecules, and balance the lattice oxygen activity. and reversibility.
An ultra-high energy density of 729.7Wh kg-1 was achieved, significantly exceeding the state-of-the-art material 638.4Wh kg-1, and improved the structural stability and cycling performance of the material.
Smart Images

Figure CN119284974A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a layered oxide material, a preparation method, and the use of a cathode material for a sodium-ion battery, belonging to the technical field of sodium-ion batteries. Background Art
[0002] Introducing Li into the cathode of a layered sodium-ion battery (SiB) + and accompanying the Na-O-Li configuration is a feasible method to trigger the redox activity of lattice oxygen. Just like the Li-O-Li configuration in lithium-rich materials, due to the non-bonding oxygen 2p orbitals, the Na-O-Li configuration can also exhibit lattice-oxygen redox activity. For example, the Na 5 / 6 [Li 1 / 4 Mn 3 / 4 O2 reported by Komaba et al. provides a reversible specific capacity of 200 mAh g -1 at 1.5 - 4.4 V. After that, other Na x [Li y Mn 1-y O2 (0 < x ≤ 1, 0 < y ≤ 1 / 3, such as Na 0.6 [Li 0.2 Mn 0.8 O2, Na 0.72 [Li 0.24 Mn 0.76 O2 have also explored Na[Li 1 / 3 Mn 2 / 3 O2 layered oxides with different crystal structures, showing high capacity through lattice oxygen redox. However, it should be noted that lattice oxygen can also show high capacity. It is oxidized to an unwanted high valence state and reacts with the electrolyte or is released from the lattice, resulting in subsequent structural rearrangement and even structural failure. Since the energy density is determined by the reduction process of the oxidized lattice oxygen during the lattice oxidation process, which is the discharge process rather than the lattice oxygen oxidation process during charging, high lattice oxygen activity does not always mean high capacity or energy. Generally speaking, although activating lattice oxygen redox is crucial for enabling layered cathodes to break through the capacity limit, irreversible redox and loss of lattice oxygen, as well as structural rearrangement and failure, are still the main obstacles to be solved. Summary of the Invention
[0003] The present invention provides a layered oxide material NLMCO, which solves the problems of irreversible redox, loss of lattice oxygen, and structural rearrangement during charging and discharging of the existing Na 0.75 [Li 0.25 Mn 0.75 O2 (NLMO), as well as the poor reversibility shown.
[0004] The technical solution is:
[0005] A layered oxide material having the following general chemical formula: Na 0.7 [Li 0.1+x Mn 0.6+y Co 0.05+z ]O 2-δ (NLMCO); 0≤x≤0.2, 0≤y≤0.2, 0≤z≤0.1; δ is the oxygen vacancy content.
[0006] The layered oxide material has the following general chemical formula: Na 0.7 [Li 0.2 Mn 0.7 Co 0.1 ]O 2-δ .
[0007] The above-mentioned layered oxide material is prepared by a solid phase method.
[0008] The solid phase method comprises the following steps: using raw materials Na2CO3, Li2CO3, MnO2 and Co2O3, mixing them uniformly according to the stoichiometric ratio, ball milling them, and calcining them at 750-850°C in an oxygen-containing atmosphere for 5-20 hours.
[0009] The ball milling conditions were 100-500 rpm for 1-10 h.
[0010] The stoichiometric ratio was determined so that Na2CO3 was in excess of 5%.
[0011] A sodium ion battery positive electrode comprises the layered oxide material.
[0012] Co is used to inhibit Na 0.7 [Li 0.1+x Mn 0.6+y Co 0.05+z ]O 2-δ (NLMCO) materials are used in irreversible phase transition, irreversible lattice oxygen oxidation, strengthening the covalent bond between transition metal and oxygen (TM-O) in oxides, and inhibiting the release of oxygen molecules during the discharge and charge cycle of sodium ion batteries; 0≤x≤0.2, 0≤y≤0.2, 0≤z≤0.1; δ is the oxygen vacancy content.
[0013] A method for inhibiting irreversible phase change of a positive electrode material of a sodium ion battery during a discharge and charge cycle of the sodium ion battery, inhibiting irreversible lattice oxygen oxidation, enhancing the covalent bond between transition metal and oxygen (TM-O) in the oxide, and inhibiting the release of oxygen molecules, comprising the following steps: preparing a sodium ion battery having a general chemical formula of Na 0.7 [Li 0.1+x Mn 0.6+y Co 0.05+z ]O2-δ Oxide material; 0≤x≤0.2, 0≤y≤0.2, 0≤z≤0.1; δ is the oxygen vacancy content.
[0014] The present invention successfully introduces cobalt into Nax[Li y Mn 1-y ]O2 system, developed Na 0.7 [Li 0.2 Mn 0.7 Co 0.1 ]O2(NLMCO) reached 729.7Whkg -1 Ultra-high energy density, significantly exceeding the state-of-the-art Na 0.75 [L i0.25 Mn 0.75 ]O2(NLMO,638.4Whkg -1 ). BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 :(a) sXRD and (b) NPD patterns of NLMCO. (c) HAADF-STEM image projected along the
[100] direction and the corresponding structural model (yellow: Na, blue: transition metals). (d) EDS spectrum of NLMCO.
[0016] Figure 2 :(a) Initial charge-discharge curves and corresponding energy densities (shaded area) of NLMCO and NLMO electrodes within 1.5-4.5 V. (c) Cycling performance and Coulombic efficiency of NLMCO and NLMO at 5 °C. (f) Na+ diffusion coefficients of NLMCO and NLMO from the initial cycle of GITT. (g) Energy density statistics of some representative SIB cathodes.
[0017] Figure 3 :The dQ / dV curves of NLMCO and NLMO at 0.1C are in the voltage range of 1.5-4.5V.
[0018] Figure 4 : Charge and discharge curves of NLMCO at different rates.
[0019] Figure 5 : In situ XRD patterns of NLMCO. (b) Changes in lattice parameters V (black dots), c (blue dots) and a / b (red dots). (c) Ex situ Mn K-edge and (d) Co K-edge XANES spectra of NLMCO during the initial charge and discharge process.
[0020] Figure 6: In situ XRD patterns of NLMCO collected during the initial two cycles at 0.2C in the voltage range of 1.5–4.5 V.
[0021] Figure 7 : (a) In situ XRD patterns of NLMO collected during the initial two cycles at 0.2C in the voltage range of 1.5–4.5 V. (b) Contour plot of the main diffraction peaks from the in situ XRD pattern of NLMO
[0022] Figure 8 : Ex situ OK-edge XAS spectra of NLMCO (i) pristine state (ii) fully charged state (4.5 V) (iii) discharged to 3.5 V state, and (iv) fully discharged state. All spectra exhibit characteristic peaks associated with lattice oxygen, whose intensities vary during charge and discharge.
[0023] Fig. 9 : a) EPR spectra of fully charged NLMCO and NLMO electrodes under the same measurement conditions. (b) EPR spectra of pristine and fully charged NLMCO electrodes. In situ DEMS-COHP spectra collected during initial charge and discharge of (c) NLMCO and (d) NLMO electrodes (e) for Mn-O and Co-O bonds of NLMCO and (f) for Mn-O bonds of NLMO. DETAILED DESCRIPTION
[0024] Lattice oxygen redox in layered metal oxide cathodes provides a promising approach for developing high energy density sodium-ion batteries. However, due to the loss of active oxygen and subsequent structural rearrangement, the oxidation and reduction of lattice oxygen are always asymmetric, resulting in poor reversibility during charge and discharge. This paper develops a layered Na-ion battery by balancing the lattice oxygen activity and reversibility. 0.7 [Li 0.2 Mn 0.7 Co 0.1 ]O2(NLMCO), which can provide a record 729.7Wh kg -1 The energy density of Na 0.75 [Li 0.25 Mn 0.75 ]O2(NLMO,638.4Wh kg -1 ). According to the results of electron paramagnetic resonance spectroscopy, in situ differential electrochemical mass spectrometry, and electrochemical tests, highly activated lattice oxygen is effectively stabilized in NLMCO without oxygen molecule release, while obvious oxygen release is detected in highly activated NLMO. The NLMCO electrode simultaneously exhibits high lattice-oxygen activity and reversibility, which originates from the enhanced transition metal-oxygen covalency and reduced band gap, resulting in excellent rate and cycling performance and ultrahigh energy density.
[0025] Material synthesis: Na was synthesized by conventional solid-state reaction method. 0.7 [Li 0.2 Mn 0.7 Co 0.1 ]O2(NLMCO) and Na 0.75 [Li 0.25 Mn 0.75 ]O2(NLMO). The raw materials are Na2CO3, Li2CO3, MnO2 and Co2O3. In order to compensate for the volatilization of Na2CO3 at high calcination temperature, an additional 5% is added. The weighed raw material powders are thoroughly mixed in a ball mill at 300 rpm for 5 h. The thoroughly mixed raw materials are calcined at 800°C for 12 h under an oxygen flow, with a heating and cooling rate of 2 degrees per minute. At the same time, Na2CO3 according to the stoichiometric amount is also prepared. 0.8 [Li 0.2 Mn 0.6 Co 0.2 ]O2 oxide material was used as a control.
[0026] Electrochemical test methods: The electrochemical tests were measured by CR2032 button cells using metallic sodium as the anode. NLMCO electrodes with a mass ratio of active material, acetylene black and polyvinylidene fluoride (PVDF) of 70:20:10 were prepared. The positive electrode was dried under vacuum at 120°C for 12 hours, and then the battery was assembled. The active material loading was 1.2-1.8 mg, and the electrode diameter was 12 mm. The battery was assembled in a glove box filled with high-purity argon (99.999%). The electrolyte was 1 mol L-1 NaClO4 dissolved in propylene carbonate, containing 5 vol% fluorinated ethylene carbonate as an electrolyte additive. Glass fiber was used as a separator for each sodium half-cell. Constant current charge and discharge tests were carried out on the half-cells at different current densities at room temperature using the Land BT2001A battery test system. 1C for all electrochemical tests corresponds to 100mA g -1 .
[0027] This invention successfully introduced cobalt into Nax[Li y Mn 1-y ]O2 system, developed Na 0.7 [Li 0.2 Mn 0.7 Co 0.1 ]O2(NLMCO), reaching 729.7Wh kg -1 Ultra-high energy density, significantly exceeding the state-of-the-art Na 0.75 [Li 0.25 Mn 0.75]O2(NLMO,638.4Wh kg -1 ). Theoretical calculations show that the introduced cobalt can enhance the TM-O covalent bond and reduce the band gap, thereby ensuring the rapid transmission of electrons in the TMO6 sheet and the reversible generation and extinction of electron holes in the lattice-oxygen during the charge and discharge process. Benefiting from the adjustment of the electronic structure, the electron paramagnetic resonance spectroscopy (EPR), in situ differential electrochemical mass spectrometry (DEMS) and constant current charge and discharge results show that the oxidized lattice oxygen with electron holes in NLMCO is effectively stabilized, and no oxygen molecule release is detected, while NLMO exhibits oxygen molecule release in the high lattice oxygen activation state, resulting in NLMCO having higher lattice oxygen reversibility than NLMO. In addition, in situ X-ray diffraction (XRD) shows that NLMCO exhibits better structural stability than NLMO due to its strong TMO6 skeleton, especially in the lattice oxygen oxidation stage. Finally, the electronic structure and crystal structure modulation of NLMCO ensure excellent redox reversibility at high lattice oxygen activity, resulting in ultra-high energy density.
[0028] In order to successfully introduce cobalt into Na 0.75 [Li 0.25 Mn 0.75 ]O2 system, NLMCO and NLMO were synthesized by a solid phase reaction method with fine-tuning of the calcination and cooling processes. The actual composition was confirmed by inductively coupled plasma optical emission spectroscopy (ICP-OES), and the detailed composition was consistent with the original design. Figure 1 Based on the Rietveld refinement results of synchrotron X-ray powder diffraction (sXRD) data shown in a, the structure of NLMCO can be well indexed to a hexagonal P2 structure with a space group of P63 / mmc. In addition, the superstructure diffraction peak at 11.2° can indicate the honeycomb order of Li and TM. Although NLMCO, NLMO and Na 0.8 [Li 0.2 Mn 0.6 Co 0.2 ]O2 shows the same phase, but Na 0.8 [Li 0.2 Mn 0.6 Co 0.2 ]O2, indicating that more cobalt could not be introduced into the structure. Neutron powder diffraction (NPD) was further performed to confirm the structure of NLMCO, such as Figure 1 The atomic-level structural features of NLMCO were studied by high-angle annular dark field (HAADF)-spherical aberration-corrected scanning transmission electron microscopy (STEM). Figure 1Energy dispersive spectroscopy (EDS) shows that the elements in NLMCO particles are well distributed, as shown in Figure 1 As shown in d. The microstructure of NLMCO was characterized by scanning electron microscopy (SEM), and the size of the flake particles was 1-3 μm.
[0029] The electrochemical performances of NLMCO and NLMO were investigated by galvanostatic charge / discharge in half-cells. Figure 2 The a intuitive comparison of NLMCO and NLMO at 1.5-4.5V, 0.1C (1C = 100mAg -1 ) The energy density under the same test conditions, where NLMCO showed 729.7Whkg in SIBs -1 The record energy density is better than NLMO (638.4Whkg -1 ). The dQ / dV curves of NLMCO and NLMO at 0.1C are as follows Figure 3 As shown, it can be seen that the capacity during charging is mainly provided by the high voltage stage, while during discharging, the capacity contribution is spread over the entire platform. The rate performance of NLMCO and NLMO is also evaluated, as shown in Figure 2 It is worth noting that the NLMCO electrode provides higher capacity than the NLMO electrode at all rates. Figure 4 The charge and discharge curves of NLMCO at different rates are shown. Specifically, at 0.1C, the discharge capacities of NLMCO and NLMO are 274.3 mAh g -1 and 244.2mAhg -1 Even at 10C, the NLMCO electrode still delivers 164.2 mAhg -1 The capacity is NLMO (74.2 mAhg -1 ). In general, NLMCO also exhibits very superior rate performance compared to NLMO. This superior performance is attributed to the increase in ionic and electronic conductivity, which facilitates timely Na+ insertion / extraction and electron transfer. Figure 2 c illustrates the cycling performance of NLMCO and NLMO electrodes at 5C, where NLMCO and NLMO deliver 173.1 mAh g during the first discharge. -1 and 147.5mAhg -1 After 100 cycles, the capacity retention rate of NLMCO is 87.3%, while that of NLMO is 64.2%. The density of states (DOS) of NLMCO and NLMO are shown in Figure 2. Figure 2 D and Figure 2as shown in e. It can be found from the figure that the band gap of NLMCO is significantly lower than that of NLMO, which indicates that the electronic conductivity of NLMCO is better than that of NLMO. In addition, it can be found that compared with NLMCO, NLMO exhibits more abundant isolated O2p states near the Fermi level, which indicates that NLMO has higher lattice oxygen activity. It is worth noting that NLMCO exhibits abundant O2p and Co3d states near the Fermi level, indicating the presence of strong Co-O covalent bonds. Strong Co-O covalent bonds will produce more delocalized TM-O bonds, thereby enhancing the lattice-oxygen stability and promoting the formation of stable oxidized lattice oxygen intermediates. Therefore, the reversibility of lattice oxygen redox in NLMCO will be improved. The constant current intermittent titration technique (GITT) was used to study the ionic conductivity of the two electrodes. According to Figure 2 In the f, the sodium ion diffusion coefficient (DNA+) data evaluated by GITT, it is clear that NLMCO outperforms NLMO in the initial charging stage accompanied by the oxidation of lattice oxygen. This can be taken as evidence of the lattice oxygen redox kinetics.
[0030] The structural evolution of NLMCO and NLMO electrodes during charge and discharge at 1.5-4.5 V was studied by in situ XRD. The diffraction peaks of NLMCO ( Figure 5 and Figure 6 ) exhibits periodic changes upon charge and discharge without any new peaks, indicating that the structural evolution is reversible. In addition, even at the fully charged state, NLMCO still exhibits high peak intensity, indicating that the NLMCO electrode has a stable structure in a wide voltage window. Figure 3 Figure b shows the change of NLMCO lattice parameters in the in-situ XRD refinement results, where the (002) and (004) peaks are related to the lattice parameter c, and the lattice parameter a / b can be related to the (100) and (102) peaks. The ultra-low changes in lattice parameters a / b (1.284%), c (1.466%), and V (1.434%) further confirm the superior structural stability and reversibility of NLMCO. In comparison, the diffraction peaks of NLMO gradually disappear in the high voltage region, as shown in Figure 2. Figure 7 As shown in Figure 2, this can be attributed to the structural rearrangement produced by irreversible lattice oxygen redox (e.g., release of oxygen molecules). Cobalt doping can significantly improve the structural stability and reversibility, achieving reversible lattice oxygen redox. In addition, regulating the lattice oxygen redox chemistry can promote the improvement of the crystal structure.
[0031] Ex situ Mn and CoK-edge XAS measurements were also performed to confirm the charge compensation mechanism, e.g. Figure 5 C and Figure 5d. It is observed that the oxidation states of Mn and Co remain essentially unchanged during the initial charge process, which means that the specific capacity in this process is provided solely by lattice oxygen oxidation, and that the original oxidation state of Mn is tetravalent, with Co exceeding trivalent. During the subsequent discharge process, Na insertion causes a negligible energy shift in the Mn / Co K-edge spectrum at around 3.5 V, indicating the absence of the involvement of Mn and Co. When the electrode is further discharged to 1.5 V, the Mn and Co K-edge spectra show a clear shift toward lower energy, indicating the involvement of Mn and Co. In particular, Mn 4+ Reduced to Mn 3+ , and Co n+ (n>3) is reduced to Co 2+ . During discharge, Mn 3+ and Co 2+ The appearance of confirms that part of the specific capacity in the low voltage region is provided by Mn and Co. Ex situ OKedgeXAS tests were also performed to explore the lattice oxygen, and the results are shown in Figure 8 shown.
[0032] To further explore the underlying cause of the increased energy density of NLMCO, EPR measurements were performed to confirm the lattice oxygen redox and were performed under vacuum at 110 K. The EPR spectra of the pristine NLMCO and NLMO electrodes were signal-free. In addition, the ex situ Mn and Co K-edge XAS data ( Figure 5 C and Figure 5 d) indicates that Mn and Co do not participate in charge compensation during the initial charging process. Therefore, the peak intensity of EPR can be reasonably attributed to the oxidation of lattice oxygen during the initial charging process. Figure 4 A and Figure 4 As shown in (b), there is a significant signal (g = 2.004) in both the fully charged NLMCO and NLMO electrodes, but not in the pristine electrode, which can be attributed to the oxidized lattice oxygen with a single unpaired electron. In particular, under the same conditions, NLMCO shows a significantly stronger peak intensity than NLMO ( Fig. 9 a), which indicates that more oxidized lattice oxygen has a single unpaired electron than the fully charged oxygen molecule in NLMCO, which ensures that the oxidized lattice oxygen can be reversibly reduced. In situ DEMS was used to detect the formation of oxygen molecules during the initial charge and discharge process of NLMCO and NLMO electrodes. When the charging potential exceeds about 4.2 V, the NLMCO electrode ( Fig. 9 c) shows no oxygen release, while the NLMO electrode ( Fig. 9 d) shows obvious oxygen release, which is consistent with the EPR result. Further crystal orbital Hamiltonian population (COHP) analysis, such as Fig. 9 E and Fig. 9As shown in Fig. f, the TM-O covalency of NLMO and NLMCO was analyzed. In the COHP analysis, positive values represent antibonding interactions, and the negative sign indicates bonding interactions. Compared with NLMO, due to the introduction of cobalt, the bonding interaction of TM-O in NLMCO is enhanced below the Fermi level. In addition, it is worth noting that during the sodiation process, the bonding interaction of TM-O in NLMO weakens, while the TM-O bonding interaction in NLMCO strengthens, indicating that the structure of NLMCO is enhanced, which can stabilize the oxidation of lattice oxygen during charging. According to the DOS results of NLMCO ( Figure 2 d), this indicates that the bonding states should be connected by π-type interactions, resulting in enhanced covalency. In NLMCO, the π-type interaction involves non-bonding O2p and Cot2g states, which can effectively stabilize the non-bonding O2p state and optimize the lattice oxygen redox. This analysis provides an in-depth understanding of the reason for introducing cobalt into the configuration, and cobalt can enhance the reversibility of lattice-oxygen redox.
[0033] The respective roles of Li and Co also reveal the intrinsic connection between lattice-oxygen reversibility and energy density. Specifically, by introducing Li into the TM layer, a Na-O-Li configuration can be formed, and the lattice oxygen in this configuration exhibits redox activity due to the non-bonding oxygen 2p orbitals. However, although the introduction of Li in the TM layer can activate the lattice oxygen, high lattice-oxygen activity does not always mean high energy density, because lattice-oxygen loss (such as the release of oxygen molecules in NLMO) occurs during the initial charging process, and the energy density is mainly determined by the reduction process of oxidized lattice oxygen (the discharge capacity of oxidized lattice oxygen O(2-n), 0 < n < 2), rather than the reduction process of lattice oxygen (the charging capacity of the original lattice oxygen O 2- ). Fortunately, the introduction of cobalt in NLMCO can enhance the TM-O covalent bond ( Figure 2 d and Figure 4 e), to stabilize the oxidized lattice oxygen ( Fig. 9 a) and inhibit the release of oxygen molecules ( Fig. 9 c), resulting in high lattice-oxygen reversibility and discharge capacity. In particular, although the discharge capacities of NLMO and NLMCO are contributed by lattice oxygen and TM, the capacities provided by TM are similar and account for a small proportion ( Figure 2 d). Finally, a high energy density is obtained by balancing the lattice-oxygen activity and reversibility in NLMCO.
Claims
1. A layered oxide material, characterized in that: It has the following general chemical formula: Na 0.7 [Li 0.1+x Mn 0.6+ y Co 0.05+z ]O 2-δ (NLMCO); 0≤x≤0.2, 0≤y≤0.2, 0≤z≤0.1; δ is the oxygen vacancy content.
2. The layered oxide material according to claim 1, characterized in that The layered oxide material has the following general chemical formula: Na 0.7 [Li 0.2 Mn 0.7 Co 0.1 ]O 2-δ .
3. The layered oxide material according to claim 1, characterized in that The space group of the layered oxide material is P63 / mmc, and it has a P2-type layered structure with hexagonal crystal characteristics.
4. The method for preparing the layered oxide material according to claim 1, characterized in that: It is obtained by solid phase method.
5. The preparation method according to claim 4, characterized in that: The solid phase method comprises the following steps: using raw materials Na2CO3, Li2CO3, MnO2 and Co2O3, mixing them uniformly according to the stoichiometric ratio, ball milling them, and calcining them at 750-850°C in an oxygen-containing atmosphere for 5-20 hours.
6. The preparation method according to claim 5, characterized in that: The ball milling conditions were 100-500 rpm for 1-10 h.
7. The preparation method according to claim 5, characterized in that: The stoichiometric ratio was determined so that Na2CO3 was in excess of 5%.
8. A sodium ion battery positive electrode, characterized in that: Contains the above-mentioned layered oxide material. 9.Co is used to inhibit Na 0.7 [Li 0.2 Mn 0.7 Co 0.1 ]O2 (NLMCO) materials are used in irreversible phase transition, irreversible lattice oxygen oxidation, strengthening the covalent bond between transition metal-oxygen (TM-O) in oxides, and inhibiting the release of oxygen molecules during the discharge and charge cycle of sodium ion batteries.
10. A method for inhibiting irreversible phase change of a positive electrode material of a sodium ion battery during a discharge and charge cycle of the sodium ion battery, inhibiting irreversible lattice oxygen oxidation, enhancing the covalent bond between transition metal and oxygen (TM-O) in the oxide, and inhibiting the release of oxygen molecules, comprising the following steps: preparing a sodium ion battery having a general chemical formula of Na 0.7 [Li 0.1+x Mn 0.6+y Co 0.05+z ]O 2-δ Oxide material; 0≤x≤0.2, 0≤y≤0.2, 0≤z≤0.1; δ is the oxygen vacancy content.